Pattern of adverse drug reactions reported to the regional Pharmacovigilance center at Nepal Medical College and Teaching Hospital, Kathmandu - Bista, Durga; Shrestha, Bal Ram; Rai, Prakash; Jauhari, Akhilesh Chandra; Kulshrestha, Vishnu Kant (Journal of Nepal Pharmaceutical Association, 2012)
The Pharmacovigilance program in Nepal is at very preliminary stage. Present study analyzed the pattern, causality, severity and preventability of the reported adverse drug reactions (ADRs) to the Pharmacovigilance center at Nepal Medical College and Teaching Hospital (NMCTH), from June 2007 to July 2011. A total of 40 ADR cases were reported, among which 23 (57.5%) were in males and 17 (42.5%) in females. Nineteen (47.5%) ADRs were reported in the age group between 21-40 years. Department of Medicine reported 12(30%) ADRs. Among the total ADRs, antibiotics [n=17, (42.5%)] were responsible for most of the reactions followed by non steroidal anti-inflammatory drugs [n=5, (12.5%)]. Most of the drugs were found to affect dermatological system [n=14, (35%)]. Carbamazepine accounted for 5 (12.5%) ADRs. The causality assessment showed 34 (85%) of the ADRs to have a ‘probable’ relationship with the suspected reaction. DOI: http://dx.doi.org/10.3126/jnpa.v26i1.6633 JNPA. XXVI(1) 2012 54-61